Effect of wind-induced internal pressure on local frame forces of low-rise buildings. (15th July 2017) - Habte, Filmon; Chowdhury, Arindam Gan; Zisis, Ioannis
Highlights: Effect of wind-induced internal pressure on building frame forces was investigated. Net frame forces highly depend on correlation between external and internal pressures. ASCE 7–10 underestimates frame forces in building with single and multiple openings. Buildings with equal sized cross-openings should be under separate enclosure category. GCpi of ±0.42 is recommended for equal sized opening on wind ward and leeward sides. Abstract: Given the significant role of internal pressures in the wind-induced loading of low-rise buildings, their correct estimation is critical for the accurate determination of the net (external plus internal) wind effects. This paper presents results of an investigation conducted to study the effect of wind-induced internal pressures on structural frame forces on low-rise buildings with single or multiple dominant openings. Models from the National Institute of Standards and Technology (NIST) aerodynamic database with internal pressure measurements were used. Large-scale experiments were also conducted in the Wall of Wind (WOW) facility at Florida International University (FIU) using a model with multiple openings. Calculations of frame forces were performed using the Database-Assisted Design (DAD) methodology. It was found that internal pressure significantly increases the forces induced by wind with the most unfavorable direction on the frames located close to the openings. However, its effect on the frames located away from the openings was smaller. Effects of internal pressure also varied between different cross-sectional locations of the same frame, depending upon the correlation between forces induced by external and internal pressures. For the highest net frame forces, the reduction factor applied to the response induced by internal pressures, that accounts for the imperfect correlation between the external and internal pressures, was found to be approximately 0.85. Comparison between frame forces calculated using experimentally measured internal pressures and their counterparts evaluated by using ASCE 7–10 provisions for internal pressures showed that the latter result in unconservative estimates of frame forces in both enclosed and partially enclosed buildings. An additional significant result is that the ASCE 7 classification of buildings with equally sized windward and leeward openings as enclosed buildings can lead to the underestimation of net frame responses. It is therefore proposed that this classification be changed to reflect the appropriate internal pressure effects.